The homology and function of the lung plates in extant and fossil coelacanths - Camila Cupello (Nature Portfolio, 2017)
Abstract The presence of a pulmonary organ that is entirely covered by true bone tissue and fills most of the abdominal cavity is hitherto unique to fossil actinistians. Although small hard plates have been recently reported in the lung of the extant coelacanth Latimeria chalumnae, the homology between these hard structures in fossil and extant forms remained to be demonstrated. Here, we resolve this question by reporting the presence of a similar histological pattern–true cellular bone with star-shaped osteocytes, and a globular mineralisation with radiating arrangement–in the lung plates of two fossil coelacanths (Swenzia latimerae and Axelrodichthys araripensis) and the plates that surround the lung of the most extensively studied extant coelacanth species, L. chalumnae. The point-for-point structural similarity of the plates in extant and fossil coelacanths supports their probable homology and, consequently, that of the organ they surround. Thus, this evidence questions the previous interpretations of the fatty organ as a component of the pulmonary complex of Latimeria.